Chemical separation of p‐ and n‐type thermoelectric chips from waste thermoelectric module and valorization through synthesis of Bi2Te3 nanopowder: a sustainable process for synthesis of thermoelectric materials. Issue 3 (26th July 2016) - Swain, Basudev; Lee, Kun‐Jae
Abstract: BACKGROUND: A laboratory scale sustainable valorization and treatment process for waste thermoelectric chips has been developed. Both p‐ and n‐type chips in thermoelectric modules are separated from the substrate through thermal treatment followed by chemical dissolution. Residual Pb‐Sn solder from separated chips is selectively dissolved by HCl. The dissolved solders are precipitated as Sn(OH)4 and Pb(OH)2 using NaOH; these are suitable for disposal without harming the environment. From the separated chips, n‐type chips are selectively separated from p‐type chips through HNO3 dissolution. The p‐type chips are passive to dissolution and are recovered without degradation, and can be reused in thermoelectric modules. RESULTS: From the dissolved n‐type thermoelectric chips from the waste thermoelectric modules, semiconductor grade, 20 nm, and 99.999% pure thermoelectric Bi2 Te3 nanopowder is synthesized through wet chemical reduction using hydrazine, and can be used to manufacture n‐type chips. CONCLUSION: The developed e‐waste management follows the cradle‐to‐cradle design which addresses cradle‐to‐grave challenges with EOL thermoelectric modules. The process is a clean, green, and techno‐economical feasible technique for treatment and remediation of hazardous soldering material and adds value through the recovery of industrially important metals such as Bi, Te, and Sb. © 2016 Society of Chemical Industry